Pelatihan Penerapan Teknologi Pendidikan untuk Meningkatkan Kualitas Pembelajaran di SD Melbourne Medan - Susanti; Gloria Sirait; Irving Josafat Alexander (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
This community service activity aims to improve digital literacy and the teaching quality of teachers at SD Swasta Melbourne, Deli Serdang Regency, through training on the implementation of digital and inclusive-based learning technology. The main issue addressed is the low level of teacher skills in utilizing digital technology to support student learning. The methods used include public education through seminars and workshops, as well as hands-on training through demonstrations and direct practice. The training materials cover inclusive teaching strategies, the use of educational digital platforms, the development of digital teaching media, and the simulation of the AllEducation application as an interactive learning tool for all learners. The results of the activity showed a significant improvement in teacher competencies based on pre–post tests and field practice, along with the production of outputs in the form of digital teaching media and the AllEducation application. Additionally, a Teacher Learning Community (KBG) was formed as a means to sustain the program. This activity contributes to addressing the challenges of implementing technology-based education at the elementary school level.